Non-opioid psychiatric medications for chronic pain: systematic review and meta-analysis - Ayub, Shahana; Bachu, Anil Krishna; Jain, Lakshit; Parnia, Shanli; Bhivandkar, Siddhi; Ahmed, Rizwan; Kaur, Jasleen; Karlapati, Surya; Prasad, Sakshi; Kochhar, Hansini; Ayisire, Oghenetega Esther; Mitra, Saloni; et al. (Frontiers in Pain Research, 2024)
BackgroundThe escalating number of deaths related to opioid usage has intensified the pursuit of non-opioid alternatives for managing chronic pain. It's often observed that psychiatric comorbidities coexist in patients suffering from chronic pain. There are a variety of psychotropic medications that have demonstrated effectiveness in treating both psychiatric symptoms and pain. This systematic review and meta-analysis aim to assess the effectiveness of various psychiatric drugs in managing specific types of chronic pain, including fibromyalgia, neuropathic pain, and chronic low back pain.MethodsA comprehensive search of five major databases was conducted through February 2023 to identify randomized controlled trials (RCTs) that met our inclusion criteria, focusing on outpatients Over 18 years of age with chronic pain. The study assessed the effectiveness of duloxetine, mirogabalin, pregabalin, gabapentin, and tricyclic antidepressants (TCAs), including serotonin-norepinephrine reuptake inhibitors (SNRIs), across various chronic pain conditions such as fibromyalgia, neuropathic pain, and chronic low back pain. The primary outcome measures included pain reduction, improvement in function, and quality of life. Of the 29 RCTs in the systematic review, 20 studies qualified for the meta-analysis. The analysis was stratified by pain type and treatment duration (short-term ≤14 weeks vs. long-term >14 weeks), using Hedge's g standardized mean differences and a random-effects model, along with sensitivity and subgroup analyses.ResultsThe overall short-term intervention effect across all studies was significant (SMD −1.45, 95% CI −2.15 to −0.75, p < 0.001), with considerable heterogeneity (I2 = 99%). For fibromyalgia, both duloxetine and mirogabalin demonstrated substantial efficacy with SMDs of −2.42 (95% CI −3.67 to −1.18, p < 0.0001) and −2.10 (95% CI −3.28 to −0.92, p = 0.0005), respectively. Conversely, treatments for neuropathic pain and chronic low back pain, including those with amitriptyline and desipramine, did not show significant benefits. The effectiveness of gabapentin could not be conclusively determined due to limited representation in the data. Additionally, no consistent long-term benefits were observed for any of the medications.ConclusionsWhile the results of this study underscore the importance of exploring non-opioid alternatives for chronic pain management, particularly in light of the opioid crisis, it is crucial to interpret the findings carefully. Our analysis suggests that certain psychiatric medications, such Duloxetine and mirogabalin demonstrated significant short-term efficacy in fibromyalgia patients. However, their effectiveness in treating neuropathic pain and chronic low back pain was not statistically significant. Additionally, the effectiveness of gabapentin and other medications, such as pregabalin for neuropathic pain, could not be conclusively determined due to limited data and high study heterogeneity. No consistent long-term benefits were observed for any of the drugs studied, raising questions about their sustained efficacy in chronic pain management. These findings highlight the need for further research to understand better the role of psychiatric medications in managing specific chronic pain conditions without prematurely concluding that they are ineffective or unsuitable for these purposes.